VOICES OF THE TRADITION: RITUALS, RELIGION, AND PERFORMATIVITY THROUGH BHOJPURI MARRIAGE SONGS - Bairagi, Sanghmitra; Rawat, Akash Kumar; Singh, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The Bhojpuri speaking region occupies a very important position in the cultural landscape of Northern India. Bhojpuri is a language spoken in eastern Uttar Pradesh and western part of Bihar. The Bhojpuri marriage songs carry with itself a very rich and layered cultural traditions. It combines with itself ritual practice, religious symbolism, social memory, gendered expressions, and performatives aesthetics. These songs are sung during various stages of wedding ceremony. They are known by different names as per the ceremonies. The songs function not only as entertainment but as a repository of cultural values, community ethics, emotional experiences, and collective identity. This paper focuses on the importance of Bhojpuri marriage songs, which can be seen as a form of ritualized performance, it is deeply embedded in in the ceremonial life of Bhojpuri region. Hence, the effort here is to explore the ritual, religion, their performance through the marriage songs. The paper also highlights that how these songs are also used as a social commentary on various issues faced by the region. Further, as these songs are sung by women, it makes them the custodians of the oral tradition and cultural continuity. The paper tries to create an understanding about how the Bhojpuri marriage songs constitute an important form of intangible cultural heritage.